Comparison of Cassini results with experiments at NASA Ames for the Enceladus plume, and calculations for a mission to Enceladus - Amin, Ranj (2009)
Enceladus is the most astonishing and remarkable moon that has been found in the Saturn system. In 2005, when the spacecraft Cassini discovered Enceladus geologically active South Pole, more studies and research started to be conducted. In the South Pole of this little icy moon, there are plumes that emanate water vapor, methane and other hydrocarbons into space. Scientists and researchers have suggested biotic or abiotic source for those species. A part of this thesis work is to study and make experiments to come to a conclusion about the source of these elements. Here, three suggested experimental simulations will be conducted, which are of thermogenic methane production, Fischer-Tropsch synthesis and the growth of methanogenic organisms in simulated Enceladus conditions. The data that were collected from the experiments would be compared to the data from the Cassini spacecraft. As a result, the comparison showed that the methane and other hydrocarbons in the Enceladus plume were more likely to be products of abiotic thermogenic. The second part of this project is to calculate the energy cost to send a spacecraft to Enceladus in order to collect some samples from the plume and bring them back to earth. The calculations showed that the mission time would be 12.2 years, when the minimum velocity change (DV) was used. Thus, the cost of DV has been calculated for the halved mission time, which was more than double the lowest. Validerat; 20101217 (root)